Adiponektin Pada Sindrom Koroner Akut Studi di Pusat Jantung Nasional ”Harapan Kita” - Bagus Ari Pradnyana; Nani Hersunarti; Santoso Karo Karo (The Indonesian Heart Association, 2007)
Objective.The association of hypoadiponectinemia and the development of obesity-related condition, including dislipidemia and coronary heart dis-ease (CHD) has been known. The results of some studies on hypoadiponectinemia as a predictor of coronary artery disease is still con-troversial. The aim of this study is to examine whether the hypo-adiponectinemia can be used as a predictor of total MACE among patients with acute coronary syndrome (ACS).Patients and methods. This a cohort study recruits 80 patients with Acute Coronary Syndrome in Emergency Department of National Car-diovascular Center Harapan Kita, Jakarta. They were followed for a me-dian follow-up of 81.48 days; the end points are re-infarct, recurrent is-chemia, heart failure and all causes of mortality. The mean age is 54.51 ± 9.02 year. Sixty-three patient is male (78.8%) and 17 is female (21.3%). The mean total cholesterol is 202.14 ± 45.10 mg/dl, mean HDL is 36.75 ± 13.56 mg/dl, mean LDL is 125.42 ± 39.26 mg/dl and mean triglycerides is 182.61 ± 104.40 mg/dl. The most common risk factors are hyperten-sion (51,3%) and smoker (53,8%). The mean adiponectin level is 8.15 ± 3.67 ug/ml. On multivariate analysis, hypoadiponectinemia (< 5.34 ug/ml) tends to associates with total MACE, though statistically insignificant, with RR of 4.33 (95% CI: 0.86 – 21.8; P = 0.075).Conclusions. These results suggest that hypoadipoadiponectinemia is not significantly associates with total MACE in those ACS patients.